DEVELOPING SELF-AWARENESS AMONG STUDENTS: AN ISLAMIC PERSPECTIVE - Rodrigue Fontaine; Gapur Oziev (European Scientific Journal, ESJ, 2014)
Modern theories of psychology and management show that people often lie to themselves and to others (Tedlow, 2010). People lie to themselves for two main reasons. First, people experience cognitive dissonance and find many excuses not to change. Second, people experience learned helplessness. They become passive, helpless individuals. In both cases, people protect their identity by modifying their memories to ensure consonance (Tavris & Aronson, 2007). Modern psychological theory distinguishes between conscious thoughts, unconscious thoughts and automatic thoughts (Kahn, 1999). We developed a modified version of a Thought Record (Greenberger & Padesky, 1995; Kahn, 1999). We explained to 120 undergraduate students how it to record their thoughts, feelings and behaviour. They were then given a non-threatening task and ask to keep records for ten consecutive days. We analysed the data and we discuss the practicality of using Thought Records so that Muslim managers may act in the workplace in accordance with Islamic ethical norms.